Political Myth as Strategic Communication: Analysis of Chinese Dream's Rhetoric and English News Media's Interpretation. Issue 1 (1st January 2016) - Zhong, Lingzi; Zhang, Juyan
ABSTRACT: Within a meaning-centered framework that integrates theories of strategic communication, political myth and the Encoding-Decoding model, this research examines the Chinese government's rhetoric and English news media's interpretations surrounding the Chinese Dream campaign. Findings show that English news media made largely oppositional readings, in contrast to the meanings encoded by the Chinese government. The research proposes that this was caused by the inherent tensions in China's rhetoric, the top-down approach of propaganda, and the anticommunism ideology of the Western media, among others. This research provides an empirical case to illustrate Hallahan et al.'s (2007) proposition that meaning and influence are two fundamental emphases of strategic communication. It also provides an operational framework for analysis of political myth, which consists of four constructs, namely ways meaning is created, meaning created, meaning interpreted, and power relations manifested.